Numerical analysis on heat transfer process in the coke oven with the multi-chamber coupling mathematical model - Kaiming Xiao; Yuming Wang; Huibiao Hu; Zhi Wen; Guofeng Lou; Fuyong Su; Ruifeng Dou; Xunliang Liu (Case Studies in Thermal Engineering, 2023)
The influence of the thermal conductivity of silica bricks on the coking process as an important component of the coking and combustion chambers is still unclear. A multi-chamber coupling mathematical model of a coke oven is developed to investigate the energy-saving effect of using high thermal conductivity silica bricks in the coke oven. The model is validated using measured temperatures of coal and flue gas bed in a coke oven in operation for a coking cycle. Temperature variation and its distribution in the coking chamber, combustion chamber, and heating wall are simulated for the coke oven using silica bricks with different thermal conductivities. The obtained results showed that compared with the use of common silica bricks, coking time of one cycle can be reduced by ∼60 min, with a decreased consumption of fuel gas by ∼4.9%. The enhancement of heat transfer from the flue gas to the heating wall and the heating wall to coal using silicon bricks with high thermal conductivity can effectively shorten not only the temperature difference between the two sides of the heating wall but also reduce the mean flue temperature of the flue gas by ∼24.5 °C.